Flowers in the attic - Andrews, V. C. (Virginia C.) (Andrews, V. C. (Virginia C.). Dollanganger family series., 2019)
The four Dollanganger children move to their grandparents house with their mother. But things are not as they seem. Their mother then locks them in an abandoned wing of the large house and tells them it's only for a few days ...